2012
DOI: 10.1186/1423-0127-19-7
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic preconditioning reduces endoplasmic reticulum stress and upregulates hypoxia inducible factor-1α in ischemic kidney: the role of nitric oxide

Abstract: BackgroundAlthough recent studies indicate that renal ischemic preconditioning (IPC) protects the kidney from ischemia-reperfusion (I/R) injury, the precise protective mechanism remains unclear. In the current study, we investigated whether early IPC could upregulate hypoxia inducible transcription factor-1α (HIF-1α) expression and could reduce endoplasmic reticulum (ER) stress after renal I/R and whether pharmacological inhibition of nitric oxide (NO) production would abolish these protective effects.MethodsK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 44 publications
3
45
0
Order By: Relevance
“…[287][288][289][290][291] Tissue damage effected by these species is augmented by intermittent hypoxia reducing renal expression of antioxidants. 292 In addition, intermittent hypoxia induces the sympathetic nervous system to increase vascular resistance, downregulates expression of the kallikrein-kallistatin vasodilator Shelley Transforming growth factor β inhibition 446 Pro-fibrotic metalloproteinase inhibition 447 Anti-fibrotic metalloproteinase activation 447 Destabilization of renal Remote ischemic pre-conditioning [384][385][386][387][388][389][390] hypoxia-inducible factor Prolyl hydroxylase inhibition 244,448 von Hippel-Lindau protein inhibition 449 pathway, and activates the renal renin-angiotensin-aldosterone system to cause vasoconstriction. [293][294][295][296][297][298][299] Together these processes conspire to produce renal fibrosis and sustained hypertension and their associated means of reducing renal oxygenation ( figure 1).…”
Section: Repeated Episodes Of Acute Kidney Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…[287][288][289][290][291] Tissue damage effected by these species is augmented by intermittent hypoxia reducing renal expression of antioxidants. 292 In addition, intermittent hypoxia induces the sympathetic nervous system to increase vascular resistance, downregulates expression of the kallikrein-kallistatin vasodilator Shelley Transforming growth factor β inhibition 446 Pro-fibrotic metalloproteinase inhibition 447 Anti-fibrotic metalloproteinase activation 447 Destabilization of renal Remote ischemic pre-conditioning [384][385][386][387][388][389][390] hypoxia-inducible factor Prolyl hydroxylase inhibition 244,448 von Hippel-Lindau protein inhibition 449 pathway, and activates the renal renin-angiotensin-aldosterone system to cause vasoconstriction. [293][294][295][296][297][298][299] Together these processes conspire to produce renal fibrosis and sustained hypertension and their associated means of reducing renal oxygenation ( figure 1).…”
Section: Repeated Episodes Of Acute Kidney Injurymentioning
confidence: 99%
“…This procedure stabilizes HIF-1α in the kidney, thereby conferring protection against a subsequent period of prolonged hypoxia. 385 Pre-conditioning by having cobalt chloride in drinking water or by breathing xenon, carbon monoxide, or isoflurane gas also stabilizes HIF-1α and confers renoprotection. [386][387][388][389][390] The clear limitation of ischemic preconditioning is that it can only be deployed against a defined episode of acute hypoxia known to be imminent, such as occurs after artery clamping in transplant surgery, or the injection of radiocontrast medium.…”
Section: A New Hypoxia Paradigmmentioning
confidence: 99%
“…It was reported that NO plays a crucial role in defending ischemic kidneys against I/R injury. 16 Besides, Cau et al 13 reported that HIF-1a accumulation protects the kidney against acute ischemic injury. The present study was undertaken to investigate whether the renoprotective mechanisms of TMZ implicated the Akt/eNOS/HIF-1a signaling pathway to reduce oxidative stress following warm renal I/R injury in rats.…”
Section: Introductionmentioning
confidence: 99%
“…The beneficial impact of early ischemic PC was dependent on nitric oxide (NO) levels, as the protective effect was abolished when NO production was inhibited before early ischemic PC application. 44 The early protective effects on ER stress could possibly be because ischemic PC leads to a pro-survival phenotype in different cells. In renal epithelial cells suffering from oxidative injury, preconditioning with ER stress caused activation of ERK1/2 signaling, accompanied by a reduction in JNK activation.…”
mentioning
confidence: 99%